2002
DOI: 10.1002/cne.10334
|View full text |Cite
|
Sign up to set email alerts
|

Changes in MAP2 and tyrosinated α‐tubulin expression in cochlear inner hair cells after amikacin treatment in the rat

Abstract: The expression of MAP2 (microtubule-associated protein 2) and of tyrosinated alpha-tubulin was investigated immunocytochemically in the cochleas of normal and amikacin-treated rats. For MAP2, two different antibodies were used: anti-MAP2ab, against the high molecular weight forms, and anti-MAP2abc, additionally against the embryonic form c. In the cochlea of the normal rat, the outer (OHCs) and inner (IHCs) hair cells were labeled for MAP2abc. The labeling was weaker in IHCs than in OHCs. The hair cells were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Worthy of note is that noise exposure also shows a change in innervation patterns (i.e., efferent neurons reinnervate the IHCs) during synaptic repair (Puel et al 1998). Similar features of innervation have also been observed with aminoglycoside intoxication (Lenoir et al 1999;Ladrech and Lenoir 2002). It might be conjectured that the projection of efferent neurons onto the hair cells favors the activity-dependent stabilization of afferent neurons by regulating hair cell excitability.…”
Section: Pathophysiological Consequencesmentioning
confidence: 85%
“…Worthy of note is that noise exposure also shows a change in innervation patterns (i.e., efferent neurons reinnervate the IHCs) during synaptic repair (Puel et al 1998). Similar features of innervation have also been observed with aminoglycoside intoxication (Lenoir et al 1999;Ladrech and Lenoir 2002). It might be conjectured that the projection of efferent neurons onto the hair cells favors the activity-dependent stabilization of afferent neurons by regulating hair cell excitability.…”
Section: Pathophysiological Consequencesmentioning
confidence: 85%
“…In that respect the association of MAP2 with MTs is very desirable. The role of MAP2 in cochlear inner hair cells of rat was experimentally examined by Ladrech and Lenior (2002). The studies of the role of myosin VIIA motor in sensory hair cells (Todorov et al, 2001) also revealed that its interaction with calmodulin and MAP-2B is regulated by Ca 2+ ions, which also could be supplied by localized pulses conveyed by actin filaments as polyelectrolytes.…”
Section: Microtubules and Microtubule-associated Proteins (Maps)mentioning
confidence: 98%
“…Among them, cytoskeletal plasticity, with proteins such as Microtubule-associated Proteins (MAPs) or activity-dependent cytoskeletal protein (Arg3.1, also known as Arc) represents an interesting molecular pathway to investigate (Ladrech et al, 2004; Panford-Walsh et al, 2008). MAP has been reported to play a key-role in several pathophysiological conditions in the cochlea, ranging from synaptic reorganization following noise overexposure in the cochlea (Ladrech et al, 2004), to reaction to aminoglycoside toxicity (Ladrech and Lenoir, 2002). Expression of several MAP isoforms (in particular the MAP2c isorform, known for its role during the development of neurons) appears to be tightly regulated during the repair processes that occur in primary auditory neurons after excitotoxic injury in the cochlea, as well as after cochlear intoxication by amikacin, one of the well-known ototoxic drug (Ladrech and Lenoir, 2002; Ladrech et al, 2004).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…MAP has been reported to play a key-role in several pathophysiological conditions in the cochlea, ranging from synaptic reorganization following noise overexposure in the cochlea (Ladrech et al, 2004), to reaction to aminoglycoside toxicity (Ladrech and Lenoir, 2002). Expression of several MAP isoforms (in particular the MAP2c isorform, known for its role during the development of neurons) appears to be tightly regulated during the repair processes that occur in primary auditory neurons after excitotoxic injury in the cochlea, as well as after cochlear intoxication by amikacin, one of the well-known ototoxic drug (Ladrech and Lenoir, 2002; Ladrech et al, 2004). In this last case, the MAP pathway has been suggested to play a key role in the survival of the remaining damaged sensory cells (Ladrech and Lenoir, 2002).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation